The 2018 Clarence Ayres Scholar An Institutional Riposte to the "After the Washington Consensus". Issue 2 (3rd April 2018) - Marangos, John
Abstract: The Washington Consensus as conceived in 1989 by John Williamson, the initiator of the term, was the foundation of the mainstream perspective on international development. The Washington Consensus consisted of a set of ten policies to be imposed through conditionality by international financial institutions on distressed developing countries. The vast criticism that ensued brought a set of policies in the form of the After the Washington Consensus (hereafter the AWC) in 2003, which designated a "new" set of policy reforms and conditionalities for developing countries. The aim of this article is to contrast the two sets of controversial policies, the original Washington Consensus and AWC, to an alternative perspective of international development based on an institutionalist approach.